Reductive Amination of 1-Hydroxy-2-propanone Over Nickel and Copper Catalysts - T. Trégner; J. Trejbal; N. Ruhswurmová; M. Zapletal (Chemical and Biochemical Engineering Quarterly, 2018)
The one-step reductive amination of 1-hydroxy-2-propanone (acetol) with ammonia to 2-aminopropanol (2-APOL) over commercial nickel and copper catalysts has been studied in the continuous fixed-bed reactor at the temperature from 130 to 220 °C and different molar ratios of reactants. It was found that the optimal molar ratios of H2/acetol and H2/NH3 regarding the selectivity of 2-APOL were 25 and 1, respectively. The highest selectivity of approx. 45 % to desired 2-APOL at total conversion of acetol was achieved in the presence of the nickel catalyst. Major by-products of amination were cis and trans isomers of 2,5- and 2,6-dimethylpiperazines. Mechanism of the formation of these and other detected and/or potential by-products is discussed. So far, unpublished mass spectra of identified by-products, such as N-substituted dimethylpiperazines or various aminoalcohols, are reported in this paper.